Working together. An occupational therapy perspective on collaborative consulation. (Kairaranga, 2008)
The focus of this study was to explore the occupational therapy consultation process used with students on the autistic spectrum attending their regular school. Individual, in-depth interviews with senior occupational therapists were employed to collect the data. Grounded theory(Glaser & Strauss, 1967; Strauss, 1987; Strauss & Corbin, 1998), a qualitative research methodology, was used to develop a high-level description and conceptual ordering as an initial step towards developing a consultation model. Constant comparative analysis of the data revealed three interactive and interdependent processes, Joining Up, Finding A Way and Walking and Talking. These processes often occur simultaneously and greatly influence each other. The central concept was identified as Working Together, which highlights the collaborative nature of the consultation process. The context of the inclusive education environment requires a strong ecological approach as an essential aspect of therapists' practice. The consultation process described uses occupational therapists' day-to-day experience and is grounded within the inclusive education setting in Aotearoa New Zealand.